A Theoretical Investigation of the Stability, Electronic, Optical, and Thermoelectric Properties of BaLiP. Issue 10 (30th June 2021) - Dusabe, Bonaventure; Dongho-Nguimdo, Guy Moise; Mohammed, Hamza A. H.; Joubert, Daniel P.
Abstract : The density functional theory and post density functional theory techniques are used to investigate the properties of BaLiP for potential applications in photovoltaic and thermoelectric (TE) applications. Density functional calculations of the cohesive energy, phonon‐dispersion, and elastic constant studies establish structural, dynamical, and mechanical stability of the compound. Density functional calculations show that BaLiP is a direct bandgap semiconductor while optical properties at the Bethe–Salpeter equation level of approximation suggest that BaLiP is anisotropic with the optical bandgaps of 2.22 and 1.59 eV for in‐plane and out‐of‐plane absorption, respectively. A maximum absorption coefficient of 4.35 × 10 5 cm − 1 for in‐plane and 5.02 × 10 5 cm − 1 for out‐of‐plane absorption in the visible range at 2.69 and 2.63 eV is found, respectively. Lattice thermal conductivity is computed using a Boltzmann transport equation approach. The calculations reveal that the average lattice thermal conductivity is 2.495 Wm − 1 K − 1 at room temperature. The figure of merit, which is the main criterion for estimating the TE potential of a material, is estimated to have a maximum of 0.6 at 1000 K at a hole carrier concentration of 10 19 cm − 3 . This study shows that BaLiP has some promise as a candidate for applications in electronics, optoelectronics, and TE applications. Abstract : Herein, the authors explore, in detail, the stability, optoelectronic, and thermoelectric (TE) properties of BaLiP using density functional theory. The main goal of this study is to estimate the dielectric constants, absorption coefficient, and figure of merit. Their calculated results show that BaLiP is a potential candidate in photovoltaic and TE applications.